2020
DOI: 10.5435/jaaos-d-20-00026
|View full text |Cite
|
Sign up to set email alerts
|

Factors in Orthopaedic Residency Decision-making for Female Applicants: A Cross-sectional Study

Abstract: Background: Orthopaedics continues to remain the medical specialty with the lowest sex diversity in the United States. Orthopaedic residency programs are highly motivated to attract the best female candidates in an effort to improve their program diversity, but no studies currently exist that examine the factors of highest importance to female applicants for orthopaedic residency selection. Methods: A two-part survey was sent to female orthopaedic resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Many women in orthopaedics have delayed childbearing because of their career choice; however, some stated it had a limited influence [9,11,24]. In one study in the United States, the mean age of women orthopaedic surgeons at the time of delivery of their first child was "considerably older" than population norms (33.1 versus 24.6 years) (Table 2) [11].…”
Section: Family Planningmentioning
confidence: 99%
“…Many women in orthopaedics have delayed childbearing because of their career choice; however, some stated it had a limited influence [9,11,24]. In one study in the United States, the mean age of women orthopaedic surgeons at the time of delivery of their first child was "considerably older" than population norms (33.1 versus 24.6 years) (Table 2) [11].…”
Section: Family Planningmentioning
confidence: 99%
“…20 Another potential barrier identified in eight studies was maternity leave. 7,10,13,17,18,[21][22][23] Data from studies carried out predominantly in the USA reported the duration of maternity leave in the female orthopaedic surgeon of 4.6 to 7.8 weeks, 10,17,26 which was greater than for the male orthopaedic surgeon (0.5 to 0.8 weeks). 10,17 Another study found that 33.14% of trainees (57/172) felt pressured by their programme or colleagues to reduce maternity/paternity leave, or not take it all together.…”
Section: Resultsmentioning
confidence: 99%
“…Gender diversity of faculty and residents, number of female residents, and number of female faculty were reported to be among the least influential factors in deciding on a residency program. 12 These findings, taken together, suggest that overall mentorship quality and opportunity in surgical fields ought to be emphasized in addition to gender diversity in order to maximize female medical student interest and successful recruitment.…”
Section: Discussionmentioning
confidence: 99%